(untitled) (Politeja, 2020)
The island of Malta has served as a strategic colony since the dawn of history. Since Phoenician and Roman times, the island has been an important base in the middle of the Mediterranean Sea. Its last colonisers, the British, spent about 180 years using the islands for their imperial needs. The official closing of the British base on 31 March 1979 heralded a new economic and social reality supposedly unhampered by the exigencies of foreigners. Two major post-memory reactions kicked in – nostalgia and aversion to ex-colonial life. The postcolonial Maltese generations exhibit a range of reactions oscillating between love and hate for the British. On the other hand, British ex-service personnel and their families have continued to feel an affinity with the island base which they had come to acknowledge as a second home. This allows for a new type of relationship between the Maltese people and their British visitors where issues of colonial post-memory are negotiated. These are seen at their best in the local tourism industry. Malta woos British tourists and goes to great effort to attract them. It uses to its advantage the colonial affinity to create an attractive destination for the British which benefits the locals and the Maltese economy. In Malta post-memory has evolved in line with necessity and expediency, where animosity, though manifestly tangible, has gradually morphed into a rather benign residue in the collective reaction to the colonial past.